Meningkatkan Pengetahuan Remaja dengan Penyuluhan dan Bimbingan Tentang Cara Menjaga Kesehatan Organ Reproduksi pada Siswa SMP Swasta Di Kecamatan Mengwi - Ni Nyoman Budiani; Gusti Ayu Surati; I Komang Lindayani; I G.A.A.Novya Dewi (Poltekkes Kemenkes Denpasar, 2019)
Teenagers have limited access to information about sexuality and reproductive health because people generally consider it taboo and are not suitable for open discussion. Introducing how to care for the reproductive organs is one of the life skills education materials. But not all students get sex education, especially about maintaining cleanliness/health of reproductive organs. The purpose of this community service activity is to find out the increase in junior high school students' knowledge about how to maintain the health of reproductive organs after receiving counseling/guidance. The target in this activity is 168 private junior high school students in the Mengwi sub-district as many as 168 people. This community service method is